2022
DOI: 10.3390/molecules28010055
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from European Propolises as Potent Tyrosinase Inhibitors

Abstract: Tyrosinase is a key enzyme in the melanogenesis pathway. Melanin, the product of this process, is the main pigment of the human skin and a major protection factor against harmful ultraviolet radiation (UVR). Increased melanin synthesis due to tyrosinase hyperactivity can cause hyperpigmentation disorders, which in consequence causes freckles, age spots, melasma, or postinflammatory hyperpigmentation. Tyrosinase overproduction and hyperactivity are triggered by the ageing processes and skin inflammation as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…One of the mechanisms that might be responsible for a decrease in melanin biosynthesis is related to the inhibition of tyrosinase, a metalloenzyme that influences the first two rate-limiting melanogenesis steps [ 42 ]. Previous studies [ 43 , 44 , 45 ] showed that natural compounds might interact differently with tyrosinase enzymes of various origins [ 46 ]. Alignment of the protein sequence of mushroom, murine, and human tyrosinase using BLAST tool [ 47 ] showed a 23.23% amino acid identity between mushroom and murine tyrosinase, a 23.42% identity between mushroom and human tyrosinase and an 85.37% identity between murine and human enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…One of the mechanisms that might be responsible for a decrease in melanin biosynthesis is related to the inhibition of tyrosinase, a metalloenzyme that influences the first two rate-limiting melanogenesis steps [ 42 ]. Previous studies [ 43 , 44 , 45 ] showed that natural compounds might interact differently with tyrosinase enzymes of various origins [ 46 ]. Alignment of the protein sequence of mushroom, murine, and human tyrosinase using BLAST tool [ 47 ] showed a 23.23% amino acid identity between mushroom and murine tyrosinase, a 23.42% identity between mushroom and human tyrosinase and an 85.37% identity between murine and human enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…TYR, MITF, TRP‐1 and TRP‐2 play important roles in melanin synthesis. After activation, TYR converts l ‐tyrosine into dopaquinone, which can be used in subsequent reactions to produce melanin 53–55 . During this process, factors secreted by keratinocytes bind to melanocyte receptors and initiate melanin synthesis, including cAMP stimulation 56,57 .…”
Section: Resultsmentioning
confidence: 99%
“…After activation, TYR converts l ‐tyrosine into dopaquinone, which can be used in subsequent reactions to produce melanin. 53 , 54 , 55 During this process, factors secreted by keratinocytes bind to melanocyte receptors and initiate melanin synthesis, including cAMP stimulation. 56 , 57 cAMP increases the expression of MITF; then upregulates the expression of TYR, TRP‐1 and TRP‐2; finally promotes melanin synthesis in melanocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The protective properties of propolis extracts are evident in human experimental in vitro skin models, where they effectively inhibit UV-induced photodamage by mitigating the occurrence of DNA strand breaks and enhancing cell viability [ 120 ]. For instance, propolis is acknowledged as a powerful inhibitor of tyrosinase, a pivotal enzyme in the melanogenesis pathway [ 121 ]. Given that UV irradiation can trigger oxidative stress leading to DNA damage and pigmentation disorders, Stavropoulou et al examined various samples of Greek propolis.…”
Section: Genomic Stabilitymentioning
confidence: 99%